2006
DOI: 10.1097/00005131-200603000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Locked Plates Combined With Minimally Invasive Insertion Technique for the Treatment of Periprosthetic Supracondylar Femur Fractures Above a Total Knee Arthroplasty

Abstract: Fixation of periprosthetic supracondylar femur fractures with a locking plate provided satisfactory results in nondiabetic patients. Diabetic patients seem to be at high risk for healing complications and infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
144
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 234 publications
(156 citation statements)
references
References 18 publications
9
144
0
3
Order By: Relevance
“…Although various treatment alternatives were performed in the hip fracture group, we included only fractures of the distal femur managed with lateral locked plating. Even though similar results have been reported for this treatment modality and retrograde nailing, locked plating is the standard treatment at our institution as it allows fixation in very distal fractures, allows use of the plate for fracture reduction, and in our experience, leads to more reliable fracture alignment [27,31,38,40].…”
Section: Discussionsupporting
confidence: 55%
“…Although various treatment alternatives were performed in the hip fracture group, we included only fractures of the distal femur managed with lateral locked plating. Even though similar results have been reported for this treatment modality and retrograde nailing, locked plating is the standard treatment at our institution as it allows fixation in very distal fractures, allows use of the plate for fracture reduction, and in our experience, leads to more reliable fracture alignment [27,31,38,40].…”
Section: Discussionsupporting
confidence: 55%
“…Locking plate provides good fixation in osteoporotic bones in elderly patients. [5][6][7] 57,58,59 Previously, implants were selected depending on fracture type, whereas the LCP system can be universally applied for the treatment of all distal femoral fractures AO type A to C with the exception of AO type B Hoffa fractures, which are preferentially stabilized using lag screw osteosynthesis. The LCP plate provides enhanced distal screw fixation, even in osteoporotic bone, at the expense of more displacement at the fracture site.…”
Section: Resultsmentioning
confidence: 99%
“…Later studies, evaluating both unicortical and bicortical diaphyseal fixation constructs, demonstrated mixed results. Some showed excellent outcomes [34][35][36] , while others demonstrated nonunion rates of 2% to 17% 18,19,37,38 . The authors of some of these studies reported late failures of diaphyseal fixation and implants but did not include them in the nonunion rates [18][19][20] .…”
Section: Discussionmentioning
confidence: 99%